2015
DOI: 10.1590/2359-3997000000101
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of central precocious puberty treatment with GnRH analogue at the Triangulo Mineiro Federal University (UFTM)

Abstract: Objective: To report our experience of treating central precocious puberty (CPP) with a GnRH analogue with respect to the final heights (FH) attained in patients who completed treatment. Subjects and methods: Among 105 records of children diagnosed with precocious puberty, 62 cases (54 girls and 8 boys), who were treated with leuprolide acetate/3.75 mg/monthly, were selected, and divided into 4 groups: group 1 (G1), 25 girls who attained FH; group 2 (G2), 18 girls who completed treatment but did not reach FH; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Continuous dosing of GnRH agonists, most commonly leuprolide, causes suppression of the pulsatile GnRH signals from the hypothalamus and promotes children reaching their full heights based on genetics [14]. Giabicani et al have established formulas to predict adult height to determine if and when treatment with GnRHa is needed [15].…”
Section: Isolated Forms Of Early Pubertymentioning
confidence: 99%
“…Continuous dosing of GnRH agonists, most commonly leuprolide, causes suppression of the pulsatile GnRH signals from the hypothalamus and promotes children reaching their full heights based on genetics [14]. Giabicani et al have established formulas to predict adult height to determine if and when treatment with GnRHa is needed [15].…”
Section: Isolated Forms Of Early Pubertymentioning
confidence: 99%
“…The current treatment of choice for CPP consists of the administration of depot GnRH analogs (GnRHa). These analogs’ clinical effectiveness has been demonstrated by several authors and includes final height improvement, regression of sexual characteristics according to Marshall and Tanner’s classification, decrease in growth velocity, and decrease in bone age (BA) advancement (3,4,12-17), as well as delaying the age of menarche (18-20). Thus, treated children develop puberty at a similar time as their peers.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that GnRHa may improve FAH in girls with CPP 3,23–26 ; this is particularly true if they were diagnosed before the age of 6 years and treated with GnRHa from Tanner stage 2–3 to chronological age 11–12 years and bone age 12–12.5 years 27 . However, the effects of GnRHa treatment are unknown in girls diagnosed between 6 and 8 years of age 3 .…”
Section: Introductionmentioning
confidence: 99%